The use of ICT in educational organizations: A quantitative analysis - raftoulis, Georgios; Koniari, Dimitra (Journal of Innovation and Research in Primary Education, 2023)
The main goal of this research is analyse the use of ICT by principals of vocational training institutes and schools of second change in Greece in the administration of these organizations. Especially, it would be examined whether leaders use ICT in their administration as well as the extend of its use.  In this survey took part, total 187 directors, both of institutes of vocational training and of schools of second change. This survey was conducted in Greece during the period April- June 2020. This period was the period of Covid-19 and one of the reason that was used only the questionnaire via e mail was the above reason.  For the purposes of this survey was used the the quantitative method using through a structured questionnaire so as to examine systematically the use of ICT. The purpose of the quantitative analysis is to discover the causes of the changes of this phenomenon through objective measurement and numerical analysis. This method through the use of numerical data, contributes to the generalization of the above, under examination topic. Having analyzing the results of the survey, it has emerged the following results: Firstly, the adequate use of ICT in administration of lifelong learning structures (LLL in advance) is considered important so as each organization can keep pace with the modern digitalized conditions. Furthermore, it leads to the reduction of unemployment as well as to the opening of each one educational organization to society the following conclusions emerged The optimist aspect is that the majority of these educational leaders judge positively the use of ICT in administration of LLL structrures. This research contributes to the acquisition of new knowledge and a better appreciation of the issue of ICT in educational organizations.